Development, Acceptability and Effectiveness of Supplementary Worksheets in Teaching Kindergarten Learners - Castañeda, Jennifer (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study aimed to develop, determine the acceptability, and evaluate the effectiveness of supplementary worksheets in teaching Kindergarten learners in selected public elementary schools in the Jalajala District, Schools Division Office of Rizal, during the School Year 2025–2026. The study employed developmental, descriptive, and experimental methods of research. The developmental method was utilized in the preparation of the supplementary worksheets aligned with the Five-Year-Old Competencies for Kindergarten Learners and the MATATAG Kindergarten Curriculum Guide. The descriptive-evaluative design was used to assess the level of acceptability of the worksheets in terms of objectives, content, organization and presentation, language and style, and usefulness and relevance. The experimental method, specifically the single-group pretest-posttest design, was applied to determine the effectiveness of the worksheets.The respondents included 30 Kindergarten teachers from eight public elementary schools in Jalajala District and 21 Kindergarten learners from Pagkalinawan Elementary School. A researcher-made questionnaire-checklist was used to gather data on the level of acceptability, while parallel forms of a 10-item pretest and posttest were administered to measure learners’ performance before and after exposure to the worksheets.Findings revealed that the developed supplementary worksheets were rated very much acceptable in all evaluated criteria. There was no significant difference in the teachers’ evaluation of the worksheets when grouped according to profile variables. Moreover, results showed a significant improvement in learners’ performance, from satisfactory in the pretest to outstanding in the posttest, indicating the effectiveness of the developed materials.The study concluded that supplementary worksheets are effective instructional tools that enhance Kindergarten learners’ performance. It is recommended that school heads support their utilization and that teachers integrate these materials regularly to enrich classroom instruction
Keywords: supplementary worksheets, kindergarten education, instructional materials development, acceptability, effectiveness, pretest-posttest design